Dialectical behavior therapy in the treatment of perfectionism: A Single case design - Gian Sugiana Sugara; Alin Puspitawati; Cucu Arumsari; Anandha Putri Rahimsyah; Muhammad Muhajirin (KONSELOR, 2023)
The primary goal of the study is to investigate the effect of dialectical behavior therapy in the treatment of perfectionism in high school students. Method research using single-case experimental research with an A-B-A design Participants consisted of three students (N = 3) who indicated non-perfectionism, maladaptive perfectionism, and mixed maladaptive perfectionism. The intervention of dialectical behavior therapy in the treatment of perfectionism was carried out in eight sessions. Treatment focused on developing mindfulness, distress tolerance, interpersonaleffectiveness, and self-regulation. Participants completed the Frost MultidimensionalPerfectionism Scale. Data were collected before, during, and after the DBT intervention. The results showed that dialectical behavior therapy was effective for dealing with maladaptive perfectionism during and after the intervention. This preliminary evidence suggests the potential feasibility of using DBT in school settings.